The benefits and impacts of mandatory charging in Ontario: Perceptions of abused women, service providers and police - Johnson, Holly; Conners, Deborah E. (Université d'Ottawa | University of Ottawa, 2017)
Highlights • Service providers express stronger support for mandatory charging policies than abused women or police. One quarter of police officers feel the policy is bad for most women most of the time. • Support for the policy increases with years of experience working in policing or community agencies. • Women reported that police laid charges in half of cases. Charges are more likely to be laid when women are in favour or were unsure whether they wanted charges, or when they were physically injured. • Women who had positive ratings of mandatory charging were those who wanted their partners charged or were unsure and police did lay charges. • One quarter of women are more likely to call police in the future now that they know about mandatory charging and a similar percentage are less willing. • Shifting the responsibility for laying charges from women to police is cited as a top benefit by all three groups. For abused women, other benefits relate to being able to leave the relationship, validation that abuse is wrong, connecting women to resources and safety. • Negative consequences for abused women include weak penalties, lack of support for abusers, and abusers’ anger at being charged. • Police are more likely than abused women or service providers to cite problems with women being unprepared for the impacts of criminal justice system involvement and women not wanting partners charged. • Participants from all three groups emphasize a need for community supports in order to achieve benefits and reduce negative consequences of the policy.
Keywords: violence against women; mandatory charging; domestic violence; policy